Komunikasi, Gaya Kepemimpinan, dan Motivasu dalam Organisasi (Communicaton, Leadership Style and Motivation in Organiation) - Agustina, Agustina; Permatasri, Dedek Ramadhani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Running an organization is not an easy thing to do.It takes a lot of elements in doing it.Of all important elements in an oganization,there is one element which can make all of the aspects work together to reach one vision in the organization.It is a leader who has the ability to communicate well and to lead effectively so that he can motivate his people to give their best.In this paper,I will explain about concepts of communication in organizations and leadership styles.Based on many concepts available,it can be concluded that there is no such thing as a fixed period of time for a leader to use a certain style of communication or a certain style of leadership.In the discussion part, the concepts do not mention any conditions that a leader should meet in order to apply a certain communication style for a certain leadership style, so that the leadership style becomes effective.To have a full understanding of communication concepts and leadership styles in organizations,we also need to learn other subjects,such as economics,laws,corporate operation, and psychology to measure a leader’s success.